Constitutionality Testing of Presidential Candidacy Thresholds in Elections Based on the Principle of Popular Sovereignty - Munir; Noenik Soekorini; Sri Astutik; Vieta Imelda Cornelis; Bachrul Amiq (Journal of International Multidisciplinary Research, 2026)
This study critically examines the constitutionality of Indonesia’s presidential candidacy threshold under Article 222 of Law No. 7 of 2017 in relation to the principle of popular sovereignty in Article 1(2) of the 1945 Constitution. The threshold requiring a party or coalition to hold 20% of DPR seats or 25% of the popular vote has been controversial for limiting voter choice and reinforcing oligarchic dominance. Using a normative legal research method, the study applies doctrinal interpretation through grammatical, systematic, historical, and teleological approaches to evaluate whether the threshold is consistent with constitutional democracy. The analysis identifies a disconnect between the legislative rule and the constitutional concept of sovereignty residing with the people, informed by theories of democracy, sovereignty, and progressive legal thought. While procedurally legitimate, the threshold lacks substantive constitutional validity because of its exclusionary impact on political participation. The study proposes four reform options: repeal, proportional adjustment, judicial reinterpretation, and constitutional amendment. These reforms would realign electoral rules with democratic principles and restore voters’ political agency. A doctrinal reinterpretation model is offered, framing the threshold as a regulatory instrument rather than a rigid barrier, advocating a legal structure that promotes inclusivity and reflects the people’s general will.